US Foreign Policy Backtracking and the Conflict with China (from 2008 till 2022) - Hendas,Mohamed; Mihoubi, Ahmed (University of Ammar Theledji -Laghouat, 2022)
Since the end of the presidency of George W.Bush, the US foreign policy has witnessed a slow shift from deep engagement to containment. This ongoing transition is leading many experts and researchers in the field of international relations to make hypotheses. This study aims at bringing to light the main aspects and causes of the switch in the US foreign policy, whether it is a sign of the end of its monopoly with the rise of China or not. In addition to analyzing how America is handling the backtracking of its hegemony along with the competition with China. To accomplish those aims, relevant data specific to the US foreign policy and its competition with China are collected, explored and analyzed. The aim is to show the signs of the US regression from the international scene to become more Westerncentered in parallel with the emergence of China as a threat to the US hegemony and the way America is dealing with this matter to safeguard its image. The study found that America’s image as the world leader is really shaken and the reason behind this recent development seems to be that it kept neglecting the rising alarms that China has revived to become a superpower. Hence, American policy-makers are engaged in a race to saveface